Recent Strategies for Strengthening and Stiffening Tough Hydrogels. Issue 8 (13th May 2021) - Ji, Donghwan; Kim, Jaeyun
Abstract : Hydrogels are major components of the human body. To replace a damaged hydrogel in the body or support/monitor its normal operation, artificial hydrogels similar to those found in nature are required. As the development of morphologically adaptable soft yet tough hydrogels such as double‐network (DN) and polyampholyte (PA) gels, they are applied to soft tissues such as the neural and epithelial tissues with elastic moduli ranging from a few pascals to several kilopascals. However, creating strong and stiff hydrogels emulating stiff load‐bearing connective tissues with elastic moduli in the MPa‐to‐GPa range remains challenging. Herein, recent strategies and potential methods for strengthening and stiffening tough DN and PA gels (such as the reinforcement addition, polymer chain alignment, and solvent exchange) as well as the reinforcing and fracture mechanisms of the resulting hydrogels are summarized. The objective is to provide some insights into the optimal strategy and method for fabricating hydrogels with a combination of strength, stiffness, and toughness, which can emulate natural load‐bearing tissues. Abstract : Strengthening and stiffening tough double‐network (DN) or polyampholyte (PA) hydrogels are a promising approach to fabricate synthetic hydrogels emulating the natural load‐bearing tissues with elastic moduli in the MPa‐to‐GPa. Herein, several strategies for strengthening and stiffening the hydrogels are summarized, and their reinforcing and fracture mechanisms are outlined, providing future directions to develop hydrogels with desirable mechanical properties.